Roux-en-Y gastric bypass-induced perturbative changes in microbial communities and metabolic pathways in rats - Yang, Jing; Chen, Lei; Shang, Xue-Ying; Chen, Yi-Lin; Zhao, Shan-Shan; Jin, Shi; Yang, Jing; Liu, Hui-Xin; Du, Jian (Frontiers in Microbiology, 2022)
Background: Obesity has become a global health and socio-economic problem because of inadequate balance between energy intake and energy expenditure. Roux-en-Y gastric bypass (RYGB) and sleeve gastrectomy (SG) were two most commonly strategy for weight loss which have been proved benefit from gut microbiota restoring. Methods: Rats were received SG, RYGB and sham operations for 10 weeks, respectively. At the end of experiment, the fecal microbiota was analyzed by 16s rRNA gene sequencing. And the shift plasma metabolism of rats underwent RYGB surgery was analyzed by untargeted metabolomics. The cross talk of microbiome and metabolites was revealed by metabolic pathway enrichment and integrated analysis. Result: The SG surgery induced modest shift of gut microbiota relative to RYGB. RYGB significantly decreased the alpha diversity, Firmicutes/Bacteroides (F/B) ratio and induced the proportion of Escherichia, Bacteroides and Akkermansia genus compared to sham and SG operations, respectively. The predicted function of gut microbiota revealed the RYGB surgery uniquely enhanced the capability of linoleic acid and sphingolipid metabolism. Further, the circulating serine, phosphatidylcholine (PC) 20:5/22:5, riboflavin, L−carnitine, and linoleic acid were evaluated after RYGB surgery. And the metabolic pathway enrichment and integrated analysis suggest the RYGB induced Escherichia, Bacteroides and Akkermansia might inhibit the sphingonine and phytosphingosine metabolism from serine and promote the PC (20:5/22:5) metabolism to produce linoleic acid. Conclusion. This comprehensive analysis not only revealed the difference of gut microbiota shift after SG and RYGB but also discovered the perturbative changes in microbial communities and metabolic pathways after RYGB surgery, which provided clues of improving the beneficial effect of RYGB in metabolic disease intervention via regulating bacterial-metabolites cross talk.